X-ray photoelectron spectroscopic investigations of Cu2O nanoparticles - Nikesh, V. V.; Mandale, A. B.; Patil, K. R.; Mahamuni, Shailaja (Materials Research Bulletin, 2005)
Cuprous oxide nanoparticles of five different sizes were obtained by electrochemical as well as chemical routes. Various capping agents were used to passivate the nanoparticles. X-ray diffraction studies show formation of single phased, cubic Cu2O nanoparticles. X-ray photoelectron spectroscopic studies indicate formation of CuO phase on the surface of Cu2O nanoparticles for uncapped as well as for those, capped by tetraoctylammonium bromide. On the other hand polyacrylamide and polyvinyl pyrrolidone capped samples did not show presence of CuO. X-ray photoelectron spectroscopy also indicates formation of a Cu2+ complex with the capping material on the surface of Cu2O nanoparticles. The results were discussed in terms of capability of passivation of various additives. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Nanostructures; Oxides; photoelectron spectroscopy; Surfaces

Novel microwave assisted sol-gel synthesis (MW-SGS) and electrochromic performance of petal like h-WO3 thin films - Kharade, Rohini R.; Patil, K. R.; Patil, P. S.; Bhosale, Popatrao N. (Materials Research Bulletin, 2012)
Use of domestic microwave oven is first time employed for chemical deposition of nanocrystalline hexagonal WO3 (h-WO3) thin films. Low cost precursors like sodium tungstate, hydrochloric acid, oxalic acid and potassium sulfate signifies cost effectiveness of this thin film fabrication route. Scanning electron microscopy images reveal formation of petal like nanodisks. A number of analytical techniques were used to characterize the WO3 petal like nanodisks, including X-ray diffraction (XRD), energy dispersive X-ray spectroscopy (EDX). X-ray photoelectron spectroscopy, FT-IR spectroscopy, Raman scattering spectroscopy, UV-visible spectrophotometry and cyclic voltammetry (CV). The X-ray photoelectron spectroscopic studies revealed 2.89 O/W atomic ratio. The electrical transport studies on WO3 thin films show semiconducting behavior with n-type semiconductivity. The value of determined coloration efficiency is 57.90 cm(2)/C. The mechanism of Li+ intercalation and deinercalation in h-WO3 matrix is proposed for enhanced electrochromism. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Chemical synthesis; Electrochemical properties; Oxides; photoelectron spectroscopy

Can we shift and/or broaden the catalysis regime towards ambient temperature? - Gopinath, Chinnakonda S.; Roy, Kanak; Nagarajan, Sankaranarayanan (ChemCatChem, 2015)
An attempt was made to shift the temperature regime of oxidation catalysis towards ambient temperatures by employing surface modification (SM) as a handle. Systematic SM of Pd(111) was performed by O-atom diffusion into the subsurfaces. Virgin and modified Pd(111) catalysts were evaluated for CO oxidation. Typical CO poisoning observed on virgin surfaces was partially lifted, and ambient CO oxidation was observed on the modified surfaces. CO oxidation was followed by the molecular beam method and near-ambient pressure (NAP) photoelectron spectroscopy under different pressure regimes. UV valence band spectral analysis of the SM and the CO+O-2 reaction on modified Pd(111) surfaces under NAP conditions demonstrated changes in the electronic structures of the surfaces with a change in surface potential by 0.35eV and directly probed CO2 formation under the reaction conditions. Supported metal catalysts may be subjected to SM and evaluated for a shift in the catalysis regime for many different reactions.
Keywords: heterogeneous catalysis; Oxidation; photoelectron spectroscopy; surface chemistry; surface modification

SBA-15-oxynitrides as a solid-base catalyst: effect of nitridation temperature on catalytic activity - Singh, Baljeet; Mote, Kaustubh R.; Gopinath, Chinnakonda S.; Madhu, Perunthiruthy K.; Polshettiwar, Vivek (Angewandte Chemie-International Edition, 2015)
Solid bases, such as SBA-15-oxynitrides, have attracted considerable interest for potential applications as catalysts in important industrial processes. Reported herein is that by simply tuning the temperature of nitridation (ammonolysis), the catalytic activity of these solid bases can be enhanced. Solid-state NMR spectroscopy and XPS studies provided the reasoning behind this change in activity.
Keywords: heterogeneous catalysis; Nanostructures; NMR spectroscopy; photoelectron spectroscopy; solid-state structures

Sustainable CO2 reduction on in (2)O(3 )with exclusive CO selectivity: catalysis and in situ valence band photoelectron spectral investigations - Mhamane, Nitin B.; Chetry, Sibo; Ranjan, Ravi; Raja, Thirumalaiswamy; Gopinath, Chinnakonda S. (ACS Sustainable Chemistry & Engineering, 2022)
This study demonstrates a sustainable catalytic CO2 conversion to near 100% CO selectivity at ambient pressure on In2O3. Critically, high CO yield could be observed at the cost of undesired methanation, using a lower than stoichiometric amount of hydrogen in the feed; 1:1 and 1:0.67 CO2:H-2 ratios exhibit 98-99.6% CO selectivity with 25-38% CO2 conversion between 773 and 873 K. CO2 and H-2 conversion under steady-state conditions at 773-873 K suggests a 1:1 ratio of adsorbed reactants (with 1:0.67 CO2:H-2 feed) on the catalyst surface, underscoring the presence of an ideal reactant composition for the reverse water-gas shift reaction, while H-2-rich feed compositions show the H-2-dominated surface. Surface electronic structure changes, under near-operating conditions, were explored with near ambient pressure photoelectron spectroscopy (NAPPES), and the interesting findings are as follows: (a) A shift in the valence band to lower binding energy, up to 0.6 eV, was observed because of electron filling at high temperatures. (b) An observation of heterogeneous nature of the catalyst surface under NAPPES measurement conditions is attributed to the generation of active oxygen vacancy (O-v) sites, which in turn changes the work function of In2O3. (c) The above changes are found to be reversible, when the reaction was stopped. Vibrational features of the reactant molecules were observed to be broadened in the active temperature window of the catalyst supporting the heterogeneous character of the catalyst surface because of dynamic O-v generation. By optimizing gas hourly space velocity, CO2:H-2 ratio, and reaction temperature, exclusive CO selectivity is possible with a H-2:CO2 ratio of similar to 0.67, which will avoid the product separation stage altogether, while minimizing the expensive H-2 in the reactant feed.
Keywords: heterogeneous catalysis; Oxygen vacancy; photoelectron spectroscopy; RWGS; Work function